Bogbladssår hos suggor : är höjden på tuber spina scapulae en riskfaktor för utveckling av bogbladssår? - Billström, Linda (SLU/Dept. of Clinical Sciences (until 231231), 2007)
Sow shoulder lesions are a common form of decubital ulcers in sows. The wounds are often bilateral and affect both loose housed and restrained sows. In most cases shoulder lesions develop after farrowing and heal after weaning. Sows that once have had decubital ulcera are however more proned to develop new wounds after the next farrowing. The problem is multifactorial and a number of risk factors have been described, including body condition, body size, parity, time spent lying down, flooring, moisture, breed, body temperature and some herd factors.